Cosmopolitanism Perspective on the Gülen Movement - Dela Restu Bumi Patriana; Gonda Yumitro (Budapest International Research and Critics University, 2022)
This article describes the development of the Gülen Movement by using the concept of cosmopolitanism as an analytical tool. The Gülen Movement itself originated from an ideology that a Turkish cleric, Fethullah Gülen, first coined. The ideology brought by Gülen includes moderate Islamic values and a progressive Islamic movement. This ideology was well received by the community so that the Gülen Movement or the Gülen Movement became a transnational-scale movement. The article method used a literature review to collect the data Harzing's Publish & Perish search engine for the article's accuracy. The Nvivo application was used to determine gaps in articles as well as to analyze previously obtained data. The Gülen movement began with Gülen's dedication to serving the community by teaching. Gülen teaches Islamic teachings while sharing his thinkings on social issues such as social inequality and tolerance between religions. This movement developed after the followers of Gülen built schools and spread his teachings through many media such as mass media. His thought began to be known in other countries, which began the transformation of the Gülen movement into a transnational cosmopolitanism movement.